A gestão das creches conveniadas do município de São Paulo: necessidades, desafios e possibilidades formativas na ação supervisora - Panizza, Mariana Fernandes (2018)
This study aimed to comprehend the needs, challenges and formative possibilities of the school management in the kindergartens affiliated to the Education Municipal System (EMS) of São Paulo and to suggest markers for the managers’ formation in the school supervision role which collaborate and qualify the educative actions built with babies and children in the Children Education. The research presented this problematization: how the school supervision may contribute to the formative needs of the school management of the kindergartens affiliated to the system. In order to develop this work, a qualitative approach was used with the aim to recognize through the narrative interview, with four subjects, two double of managers (Direction and Pedagogical Coordination), inspired in the theories of Josso (2004, 2007); Souza (2007); André (2008). The historical contextualization of the kindergartens in the city of São Paulo was supported by authors as Haddad, Campos and Rosemberg (1991), Sanches (2003), Kulmann Jr. (1998) and Franco (2012 and 2015). The comprehension about the meaning of the childhood was based on Arroyo (1994). In order to discuss the continuing education and the school management, the theoretical assumptions of Nóvoa (2002, 2007 and 2009), Garcia (1999), Souza and Placco (2015), Salmaso (2012), Rangel (1998), Possani (2012) and Libâneo (2001) were used. The analysis of the narratives was made from the needs, challenges and formative possibilities presented by the managers. This study resulted in markers to a formative proposal which, through an integrated schedule between the kindergarten, the pedagogical department of the Regional Education Directory and the School Supervision, contemplate the kindergartens’ scarce formation in order to overcome the challenges, therefore we highlight conceptions and intentions which need to be present in the formative proposal